Circular Polarization and Wavelength Selective Gratings Based on Holographic Cholesteric Liquid Crystal Templates. (3rd October 2018) - Chin, Hsien-Kuo; Kuo, Hui-Ying; Zheng, Yang-Chen; Lin, Jia-De; Lee, Chia-Rong
Abstract : Refilling cholesteric liquid crystal (CLC) template gratings with circular polarization, wavelength selectivity, and dual operation mode are first demonstrated. The gratings with template and nontemplate regions are obtained through the two-beam interfering photo-polymerization, washing-out, and refilling procedure. The refilling CLC has different chiral handedness (left or right) and reflection band (at green and red regions). When the wavelength of a probe beam is within the refilled CLC reflection band of the nontemplate region, the device works as an amplitude grating since the sample in the template and nontemplate regions reflects distinct colour region. In addition, the diffraction intensity of the grating can be electrically controlled. Therefore, this CLC-based device can be potentially used in controllable diffraction elements in optics.